P.091 Intracerebral hemorrhage secondary to multiple myeloma: a systematic review. (17th June 2016) - Kameda, M; Koziarz, A; Aref, M; Badhiwala, J; Reddy, K; Almenawer, SA
Abstract : Background: Multiple myeloma (MM) as a cause of spontaneous intracranial hemorrhage has not been well established. Methods: We report a patient who developed a spontaneous intracerebral hemorrhage secondary to MM and conduct a systematic review of the literature. In addition, we discuss the underlying pathophysiology.Results: A 67-year-old relatively healthy female with a recent history of low back pain presented with an altered level of consciousness and left sided hemiplegia. CT demonstrated a large right temporal intracerebral hemorrhage. CT angiogram ruled out a vascular abnormality; however, multiple abnormal bony lesions were incidentally noted. Other causes for intracranial bleed were ruled out. She underwent a craniotomy for hematoma evacuation. Intra-operatively, the skull was noted to be abnormal and hematoma was not associated with a mass lesion. In addition, serum and urine electrophoresis were found to be positive for monoclonal free kappa light chains. Subsequent bone biopsy confirmed the diagnosis of MM. Our literature search identified 2 reported cases of spontaneous subdural hematomas and 2 patients with spontaneous intracerebral hematomas secondary to MM. Moreover, only 4 reports in the literature document intracranial hemorrhage secondary to a mass developed from MM.Conclusions: Multiple myeloma is perhaps an under-reported possible cause for spontaneous intracerebral hematoma.